2009
DOI: 10.5713/ajas.2009.r.06
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Nutrition of the Calf and Its Consequences for Lifelong Productivity

Abstract: Feeding cows to support the protein, energy, vitamin and mineral requirements of the growing conceptus is now recognised as just one factor that influences the life-long

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Risk of calf mortality increases drastically with delay in colostrum feeding (Zucali et al, 2013) due to inadequate passive transfer of immunoglobulin through the gut which may subsequently suppresses disease resistance capacity of calves (Godden, 2008). Superscripts are put based on z-test: z value between large and medium = 2.338; P = 0.019; z value between large and medium = 2.164; P = 0.03; z value between large and small = 4.611; P = <0.001 Deworming has also been considered as one of the factors associated with calf mortality (Wynn et al, 2009) and same being observed in our study. Deworming of dam at the last stage of pregnancy significantly reduced calf mortality (r = -0.167, P=0.034).…”
Section: Factors Associated With Calf Mortalitymentioning
confidence: 86%
“…Risk of calf mortality increases drastically with delay in colostrum feeding (Zucali et al, 2013) due to inadequate passive transfer of immunoglobulin through the gut which may subsequently suppresses disease resistance capacity of calves (Godden, 2008). Superscripts are put based on z-test: z value between large and medium = 2.338; P = 0.019; z value between large and medium = 2.164; P = 0.03; z value between large and small = 4.611; P = <0.001 Deworming has also been considered as one of the factors associated with calf mortality (Wynn et al, 2009) and same being observed in our study. Deworming of dam at the last stage of pregnancy significantly reduced calf mortality (r = -0.167, P=0.034).…”
Section: Factors Associated With Calf Mortalitymentioning
confidence: 86%
“…Low growth performance, poor reproductive performance and milk yield have been reported in buffaloes in other studies [64,65]. Indeed, the poor performance reported by those studies correlated with poor dry matter intake and weight gain and longer calving intervals [64,65].…”
Section: Supplementation Strategymentioning
confidence: 79%
“…Low growth performance, poor reproductive performance and milk yield have been reported in buffaloes in other studies [64,65]. Indeed, the poor performance reported by those studies correlated with poor dry matter intake and weight gain and longer calving intervals [64,65]. In many parts of Asia, inadequate and irregular availability of quality feedstuffs and their utilization are the main causes of the poor performance of buffaloes [44].…”
Section: Supplementation Strategymentioning
confidence: 91%
“…These conditions may be improved by be er nutrition and management of heifers (Qureshi et al, 2002;Zicarelli et al, 2007) and male buff aloes (Sahoo et al, 2004;Wynn et al, 2009). Eff ect of inclusion of palm oil solid waste in the diet to increase MEI therefore should be studied to look at the eff ect on heifers as well as on male buff aloes.…”
Section: Birth Weight and Calve Growthmentioning
confidence: 99%